Remote scoring models of rigidity and postural stability of Parkinson’s disease based on indirect motions and a low-cost RGB algorithm - Ma, Ling-Yan; Shi, Wei-Kun; Chen, Cheng; Wang, Zhan; Wang, Xue-Mei; Jin, Jia-Ning; Chen, Lu; Ren, Kang; Chen, Zhong-Lue; Ling, Yun; Feng, Tao (Frontiers in Aging Neuroscience, 2023)
Background and Objectives The Movement Disorder Society’s Unified Parkinson’s Disease Rating Scale Part III (MDS-UPDRS III) is mostly common used for assessing the motor symptoms of Parkinson’s disease (PD). In remote circumstances, vision-based techniques have many strengths over wearable sensors. However, rigidity (item 3.3) and postural stability (item 3.12) in the MDS-UPDRS III cannot be assessed remotely since participants need to be touched by a trained examiner during testing. We developed the four scoring models of rigidity of the neck, rigidity of the lower extremities, rigidity of the upper extremities and postural stability based on features extracted from other available and touchless motions. Methods The RGB (red, green, blue) computer vision algorithm and machine learning were combined with other available motions from the MDS-UPDRS III evaluation. A total of 104 patients with PD were split into a train set (89 individuals) and a test set (15 individuals). The light gradient boosting machine (LightGBM) multiclassification model was trained. Weighted kappa (k), absolute accuracy (ACC±0) and spearman correlation coefficient (rho) were used to evaluate the performance of model. Results For model of rigidity of the upper extremities, k=0.58 (moderate), ACC±0=0.73, rho=0.64(moderate). For model of rigidity of the lower extremities, k=0.66 (substantial), ACC±0=0.70, rho=0.76(strong). For model of rigidity of the neck, k=0.60 (moderate), ACC±0=0.73, rho=0.60(moderate). For model of postural stability, k=0.66 (substantial), ACC±0=0.73, rho=0.68 (moderate). Conclusion Our study can be meaningful for remote assessments, especially when people have to maintain social distance, e.g., in situations such as the coronavirus disease 2019 (COVID-19) pandemic.